Management of shadow banks for economic and financial stability in South Africa - Kehinde Damilola Ilesanmi; Devi D. Tewari (Cogent Economics & Finance, 2019)
The global increase in the regulation of banks has encouraged the channeling of investment funds into less regulated institutions such as shadow banks to avoid restriction. Shadow banks are institutions that operate outside the regulatory framework of the traditional banking system and because of that, they lack adequate safety compared to the traditional banks. These among others have raised serious concerns, especially after the recent financial crisis as they see these institutions as a major source of risk and instability in the financial system and the economy as a whole. This study examined the link between shadow banking and financial stability in South African by employing a modest desktop literature review approach. Although the shadow banking in South Africa is advantageous in terms providing alternative source of credit to support economic activities by extending banking services and investment opportunities to the unbanked as well as those who lack knowledge of how to access capital, however, issues of regulations, management and transparency have not been adequately dealt with. These create a great risk to the economy if not properly addressed. Protecting the interest and investment of customers should be a major concern of government or regulatory authorities without necessarily jeopardising the interest of shadow banking operators. Also, a proper risk measurement technique that fits the shadow banking system is necessary.
Keywords: G1; G2; O1; O5; 330; financial stability; management; shadow banking; South Africa; regulation